Small effects of olfactory identification and discrimination on global cognitive and executive performance over 1 year in aging people without a history of age-related cognitive impairment - Martinec Nováková, Lenka; Georgi, Hana; Vlčková, Karolína; Kopeček, Miloslav; Babuská, Anna; Havlíček, Jan (Physiology & behavior, 2024)
Olfactory and cognitive performance share neural correlates profoundly affected by physiological aging. However, whether odor identification and discrimination scores predict global cognitive status and executive function in healthy older people with intact cognition is unclear. Therefore, in the present study, we set out to elucidate these links in a convenience sample of 204 independently living, cognitively intact healthy Czech adults aged 77.4 ± 8.7 (61-97 years) over two waves of data collection (one-year interval). We used the Czech versions of the Montreal Cognitive Assessment (MoCA) to evaluate global cognition, and the Prague Stroop Test (PST), Trail Making Test (TMT), and several verbal fluency (VF) tests to assess executive function. As a subsidiary aim, we aimed to examine the contribution of olfactory performance towards achieving a MoCA score above vs. below the published cut-off value. We found that the MoCA scores exhibited moderate associations with both odor identification and discrimination. Furthermore, odor identification significantly predicted PST C and C/D scores. Odor discrimination significantly predicted PST C/D, TMT B/A, and standardized composite VF scores. Our findings demonstrate that olfaction, on the one hand, and global cognition and executive function, on the other, are related even in healthy older people.
Keywords: Smell; testy pro posouzení mentálních funkcí a demence; diskriminace (psychologie); čichová percepce; Humans; neuropsychologické testy; lidé středního věku; kognice; Odorants; Female; Aged; stárnutí; senioři; lidé; Aging; Discrimination, Psychological; odoranty; exekutivní funkce; čich; Neuropsychological Tests; ženské pohlaví; Male; Middle Aged; Cognitive Dysfunction; Olfactory Perception; Aged, 80 and over; senioři nad 80 let; Mental Status and Dementia Tests; Executive Function; mužské pohlaví; Cognition; kognitivní dysfunkce